Upaya Peningkatan Prestasi Belajar Peserta Didik - Fattara Diwa Serin (Journal on Education, 2023)
Students as the most important component in the educational process, should get good service and education system in order to increase their potential to produce learning achievement. One of the factors that affect learning achievement is environmental factors. This research aims to provide knowledge regarding the efforts that schools can do to improve learning achievement. The method in this research is literature study with descriptive method. Schools as places where the learning process takes place, can apply several efforts to improve student learning achievement through planning and implementing student management, school/madrasah management, good classroom management, creating innovative strategies from school principals, and improving the quality of educators and education staff in schools. These efforts are expected to be planned, socialized and implemented properly in schools in order to get better student learning achievement. Another thing that needs to be considered and must be done is evaluation activities in the school environment, through internal school meetings which can then be continued with the implementation of evaluation monitoring meetings.